Cell adhesion molecules E-cadherin and CADM1 are differently expressed in canine inflammatory mammary cancer. (20th December 2022) - Alonso-Diez, A.; Affolter, V.K.; Sevane, N.; Dunner, S.; Valdivia, G.; Clemente, M.; De Andrés, P.J.; Illera, J.C.; Pérez-Alenza, M.D.; Peña, L.
Abstract: Human inflammatory breast cancer (IBC) and canine inflammatory mammary cancer (IMC) are the most aggressive and lethal types of mammary tumors with specific characteristics such as exacerbated angiogenesis, lymphangiogenesis and lymphangiotropism. E-cadherin expression is another specific feature of IBC not previously studied in canine IMC. In this study, the expression of E-cadherin and CADM1 (Cell Adhesion molecule 1) and their possible role as key molecules involved in the pathogenesis of IMC were immunohistochemically analyzed in 19 canine IMC and 15 grade III non-IMC cases. E-cadherin and CADM1 expression was higher in IMC cases ( p  = 0.002, p  = 0.008, respectively). In the IMC group, E-cadherin cytoplasmic immunolabeling was more frequent ( p  = 0.035) and it was associated to the expression of the angiogenic and lymphangiogenic factors COX-2 ( p  = 0.009), VEGF-A ( p  = 0.031) and VEGF-D ( p  = 0.008). The differential mRNA expression between IMC and non-IMC was studied by microarray analysis in 6 cases. E-cadherin gene (CDH1) was not up-regulated in IMC cases at a transcriptional level; interestingly CADM1 was 7-fold upregulated. The differential expression of E-cadherin protein in IMC suggests a possible role of E-cadherin in the characteristic exacerbated angiogenesis and lymphangiogenesis and further support IMC as a natural model for the study of human IBC. Future studies in IBC and IMC including a broad panel of adhesion molecules are necessary to elucidate their role in the metastatic process and angiogenesis. Highlights: IBC/IMC, the most lethal mammary cancer, has distinct clinicopathological features. Changes in cell adhesion molecules contribute to tumor dissemination and metastasis. E-cadherin expression is a specific feature of human inflammatory breast cancer. As human disease, E-cadherin is expressed in IMC. Other cell adhesion molecules as CADM1 may be involved in the inflammatory phenotype.